Optimization Method for Bioethanol Production from Giant Cassava (Manihot esculenta var. Gajah) Originated from East Kalimantan - Krishna Purnawan Candra; Kasma Kasma; Ismail Ismail; Marwati Marwati; Wiwit Murdianto; Yuliani Yuliani (Universitas Gadjah Mada, 2019)
Here is the first report of bioethanol production from giant cassava, a variety of cassava originated from East Kalimantan. Hydrolysis on freshly grated cassava with two different acids was studied separately. The experiment was conducted as a single factor experiment in Completely Randomized Design (CRD) with five treatments (0.0–1.0 M of acid solution), each replicated three times. Reducing sugars, unhydrolyzed substance (fibers), and hydrolysate clarity was determined. The experiment was continued by studying fermentation condition using factorial experiment (2 x 4) in CRD. The first factor was starter concentration (Saccharomyces cerevisiae, 5 and 10%) and the second factor was fermentation time (2–11 days). Biomass and alcohol content in fermentate were determined. The data were analyzed by ANOVA, excluding alcohol content that analyzed by the non-parametric statistic. Optimization using regression analysis showed that hydrolysis by HCl was more effective than H2SO4. Hydrolysis solution of 0.58 M HCl gave an optimum reducing sugar in hydrolysate (5.6%), which equivalent to a yield of 28.18%. Starter concentration affected significantly on biomass and alcohol content (p < 0.001) of fermentate, while fermentation time affected significantly only on alcohol content (p < 0.001). Optimum condition of cassava hydrolysate fermentation (100 mL) was using 5% yeast for 8 days, which gave a yield of 14.17% bioethanol.